1985
DOI: 10.1115/1.3247422
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Turbulators for Fire Tube Boilers

Abstract: This paper summarizes an experimental study of three popular “turbulator” inserts for fire tube boilers. An electrically heated flow facility was developed to deliver hot air to a water-cooled steel tube instrumented to derive sectional average heat transfer coefficients for four regions of the tube. Reference data for the empty tube are in excellent agreement with the accepted correlation. Two commercial turbulators, consisting of narrow, thin metal strips bent and twisted in zig-zag fashion to allow periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…For a fully developed laminar flow, they found that the Nusselt number is nine times larger than that of a tube without turbulators under similar heating conditions. Junkhan et al [5] experimentally studied the effect of different turbulators installed at the tube inlet of a fire tube boiler, and observed considerable increase in heat transferred to water. Yildiz et al [6] studied the effect of a twisted strip profile used as the turbulator inside a concentric double-pipe heat exchanger.…”
Section: Introductionmentioning
confidence: 98%
“…For a fully developed laminar flow, they found that the Nusselt number is nine times larger than that of a tube without turbulators under similar heating conditions. Junkhan et al [5] experimentally studied the effect of different turbulators installed at the tube inlet of a fire tube boiler, and observed considerable increase in heat transferred to water. Yildiz et al [6] studied the effect of a twisted strip profile used as the turbulator inside a concentric double-pipe heat exchanger.…”
Section: Introductionmentioning
confidence: 98%
“…The strength of reverse flow and the reattached position are the main interest in many heat transfer applications such as heat exchangers, combustion chambers, gas turbine blades, and electronic devices. Junkhan et al [1] reported the heat transfer with several types of turbulators located in a tube to provide energy savings. Promvonge and Eiamsa-ard [2] experimentally studied the effects of the conical turbulator combined with the snail entrance on heat transfer rate and flow friction in a heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer enhancement using several types of the turbulence promoters mounted in a tube has been extensively studied for the past decades [1]. Ayhan et al [2] carried out experimental and numerical works to study the heat transfer in a tube fitted with truncated hollow cone turbulators.…”
Section: Introductionmentioning
confidence: 99%